Prediction model for mercury transfer from soil to corn grain and its cross-species extrapolation - Hai-yan HU; Zhao-jun LI; Yao FENG; Yuan-wang LIU; Jian-ming XUE; Murray Davis; Yong-chao LIANG (Journal of Integrative Agriculture, 2016)
In this study the transfer characteristics of mercury (Hg) from a wide range of Chinese soils to corn grain (cultivar Zhengdan 958) were investigated. Prediction models were developed for determining the Hg bioconcentration factor (BCF) of Zhengdan 958 from soil, including the soil properties, such as pH, organic matter (OM) concentration, cation exchange capacity (CEC), total nitrogen concentration (TN), total phosphorus concentration (TP), total potassium concentration (TK), and total Hg concentration (THg), using multiple stepwise regression analysis. These prediction models were applied to other non-model corn cultivars using a cross-species extrapolation approach. The results indicated that the soil pH was the most important factor associated with the transfer of Hg from soil to corn grain. Hg bioaccumulation in corn grain increased with the decreasing pH. No significant differences were found between two prediction models derived from different rates of Hg applied to the soil as HgCl2. The prediction models established in this study can be applied to other non-model corn cultivars and are useful for predicting Hg bioconcentration in corn grain and assessing the ecological risk of Hg in different soils.